2013
DOI: 10.3791/50622
|View full text |Cite
|
Sign up to set email alerts
|

Automated High-throughput Behavioral Analyses in Zebrafish Larvae

Abstract: We have created a novel high-throughput imaging system for the analysis of behavior in 7-day-old zebrafish larvae in multi-lane plates. This system measures spontaneous behaviors and the response to an aversive stimulus, which is shown to the larvae via a PowerPoint presentation. The recorded images are analyzed with an ImageJ macro, which automatically splits the color channels, subtracts the background, and applies a threshold to identify individual larvae placement in the lanes. We can then import the coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…During the first 15 minutes, behaviors are analyzed without visual stimuli. During the subsequent 15 minutes, behaviors are analyzed in the presence of an aversive visual stimulus, a red moving bar, which the larvae avoid [21, 25]. We found that day 3 cyclosporine exposures affected the avoidance response (Fig 7A), swim speed (Fig 7B), resting (Fig 7C), the average distance between larvae (Fig 7D), the percentage of time that larvae are close together (Fig 7E), and the percentage of time the larvae spend on the edge of the swimming area (Fig 7F).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the first 15 minutes, behaviors are analyzed without visual stimuli. During the subsequent 15 minutes, behaviors are analyzed in the presence of an aversive visual stimulus, a red moving bar, which the larvae avoid [21, 25]. We found that day 3 cyclosporine exposures affected the avoidance response (Fig 7A), swim speed (Fig 7B), resting (Fig 7C), the average distance between larvae (Fig 7D), the percentage of time that larvae are close together (Fig 7E), and the percentage of time the larvae spend on the edge of the swimming area (Fig 7F).…”
Section: Resultsmentioning
confidence: 99%
“…The 5 dpf larvae receive nutrients from their yolk sac and effects of feeding can be avoided at this time [21]. The larvae were imaged with a custom-built imaging system, as described previously [24-25]. In summary, the system includes a 15 megapixel Canon EOS Rebel T1i digital camera and an Acer Aspire 5517 laptop with a 15.6 inch screen to provide visual stimuli to the larvae.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The zebrafish is an excellent model to study the developmental effects of low levels of pesticides or other toxicants in order to determine behavioral and morphological changes after exposure (Eddins et al, 2010; Levin et al, 2011; Richendrfer and Creton, 2013; Richendrfer et al, 2014; Richendrfer et al, 2012b). Zebrafish embryos develop outside of the mother and can be collected daily in very large numbers and the embryos can be treated directly in a petri dish with various toxicants, drugs, or pesticides.…”
Section: Introductionmentioning
confidence: 99%